Analysis of Needs and Service Capacity of BPJS at First-Level Healthcare Facilities in Bandung District - Rahmah, Rizki Amalia; Basri, Mursyid Hasan (Journal of Indonesian Health Policy and Administration, 2024)
The community's need for BPJS services at Primary Health Facilities (FKTP) can be well met if adequate service capacity is available. This research aims to analyze the gap between the needs and capacity of BPJS services in FKTPs in Bandung District. This quantitative study uses secondary data owned by Dinas Kesehatan Provinsi Jawa Barat and BPJS Kesehatan Kantor Cabang Soreang. The calculation of needs uses the number of BPJS participants registered in each FKTP, and the calculation of service capacity is based on the duration of service and the number of general practitioners in the FKTP. Out of the 187 FKTPs analyzed, 125 FKTPs are experiencing overcapacity, 58 FKTPs are under capacity, and 4 FKTPs are optimal. FKTPs with optimal conditions have an average ratio of doctors to BPJS participants of 1:6250. The gap between needs and capacity will impact the quality of service and the financial health of these FKTPs. This issue needs to be addressed by redistributing the number of BPJS participants registered in FKTPs so that the primary healthcare needs of the community in Bandung District can be met.